Growth Parameters of Exclusively Breastfed versus Non-Exclusively Fed Infants in the First 5 Months of Life before Introduction of Semi-Solid Foods - Gauchan, Eva (Birat Journal of Health Sciences, 2021)
Introduction: Exclusive breast-feeding has many advantages over nonexclusive feeding; better growth and lower risks of infections being most important. The aim of this study was to find the hospital prevalence of exclusive breast-feeding, find any differences in growth and morbidity patterns in babies who were exclusively breast-fed as compared to those who were not.Methodology: This was a hospital-based cross-sectional study over a period of one year which enrolled infants 1.5 months, 2.5 months, 3.5 months and 5 months of age who were on exclusive breast-feeding or non-exclusive feeding and who had not been started on semi-solid foods. Growth and morbidity patterns were recorded. Statistical analysis was done by SPSS version 25. Continuous variables were reported as median [IQR] while categorical variables were reported as absolute number (%). Mann-Whitney U test and Chi-square test were used to find the level of significance respectively.Results: The hospital prevalence of exclusive breast-feeding was found to be 62%. Weight for age was significantly higher in infants who were on exclusive breast-feeding (p=